EVALUATION PERFORMANCE GENOTYPES OF BREAD WHEAT TO YIELD, YIELD COMPONENTS, BIOLOGICAL YIELD AND HARVEST INDEX - & Dhahi, Baktash (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2018)
A field experiments were carried out at Abu- Graib Research Station- Agricultural Research Office- Ministry of Agriculture, during the season 2014- 2015 to investigate the performance of 225 pure lines of bread wheat (Triticum aestivum L.), which at sixth generation after crossing among local and exotic genotypes (produced from 2008 to 2014) with their parents. The experiment was conducted using Simple Lattice Design with three replications. The objective of this experiment to evaluate those genotypes for yield and its components. The results were revealed highly significant differences among genotypes in all studied traits. The genotype 99 gave higher number of spikes plant-1 (44.8 spike), genotype 186 superior in grains number spike-1 (82 grain), a higher weight of grain (49.5g) produced by genotype 17 and a higher weight of grains plant-1 (82.8g) produced by genotype 99. The genotypes 149 and 189 gave higher biological yield (90g) plant-1, but the higher percentage of harvest index (46.2%) achieved at genotype 75.